Analisis dampak pandemi covid-19 terhadap usaha kerajinan tenun Toraja - Matasik, Ade Lisa; To’alla’, Verti; Mantong, Agustinus; Tangdialla, Randi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the impact of the Covid-19 pandemic on the Toraja weaving craft business in the Unnoni weaving group, Lembang Sa'dan Tiroallo, Sa'dan District, North Toraja Regency. By using this type of quantitative research, data collection techniques are carried out by means of observation, interviews and documentation by comparing the income data of the Unnoni weaving group before and during the Covid-19 pandemic using trend analysis from 2018-2021. The results show that the impact of the Covid-19 pandemic has caused a decrease in income for the Toraja Weaving handicraft business of the Unnoni Group which has also affected the performance of the business. The chain of Covid-19 distribution has resulted in the Toraja people having to stop all their activities, especially at the rambu tuka' and rambu solo' events which usually make their weaving crafts much in demand by buyers, but because of this, there are no orders for cloth and it creates business income. weaving craftsmen decreased and hampered the business.